Performing Wagner a singer's perspective on the major tenor roles - Gould, Stephen 1962-2023 (Toccata Press, 2024)
Offers a unique perspective in to what it takes to perform Richard Wagner's operas.Performing Wagner studies each of the iconic Wagnerian heldentenor roles from the unique perspective of the performer. Stephen Gould studied and acted them hundreds of times in scores of productions around the world prior to his passing in 2023. In this thoughtful book, he offers insights to building a character, understanding the dramatic arc of each role, analysing each scene for cogency and dramatic structure, and finding the clues embedded in the music and the words. His intelligence and eloquence offer perspectives that only a performer can experience. The book is unique in opera literature. Neither a memoir nor a musical analysis, Performing Wagner is a practical guide to preparing for, and performing, these roles. Stephen Gould hoped to share his experiences with enthusiasts of Wagner's works, as well as opera audiences more generally who seek to learn what singing actors do in performance. It is invaluable to young artists approaching this repertoire and to scholars studying Wagner's dramaturgy. More broadly, this volume speaks to the condition of every opera fan who has ever been floored by a great performance and wondered, 'how did they do that?'A chapter is devoted to each role, and a foreword is provided by Katharina Wagner, the composer's great-granddaughter and Director of the Wagner Festival in Bayreuth, Germany